Study On Promote Occupational Safety And Health Practices In Construction Projects - Haryati Binti Shafii,; Ebrahim Awadh Bin-Shahna,; Sharifah Meryam,; Azlina Md Yassin, (Journal of Technology Management and Business, 2019)
Abstract: The unsatisfactory OSH record of the construction industry has always been highlighted. It is because the OSHP system is a neglected area and a function that has not been pursued systematically in the construction industry. Safety is an important issue, but many employers do not feel it is vital to the success of companies. For a long time, the construction industry has been labeled as with poor OSHP and performance, which needs stern attention and in-depth research to put forward solutions to this issue. The objectives of this research are to investigate problems of OSHP in construction projects, to study the benefits of OSHP in construction projects and to recommend measures to promote OSHP in construction projects. The research was take place in Johor Bahru the capital of Johor State. The research based on quantitative research by using questionnaire to carry out the research. The questionnaire was designed based on the objectives each objective has ten statements with one option, in order to get accuracy results. A total of 67 questionnaires were gathered from a total of 217 contractors of G7 distributed at Johor Bahru, where the respondents were project manager, site supervisor, safety officer and site engineer. Data collected was analysed using the Statistical Package for the Social Science 22.0 software. The method of analysis that had being used in this research is percentage, frequency and means score value. The study proves that there are OSHP problems faced by contractors; workersâ€™ attitude, insufficient budget allocated, lack of enforcement of safety policies, less management support, etc. Moreover, there is high benefits of OSHP when its implement well; increase responsibility, higher on employees morale, build a positive work place environment, reduce rate of absenteeism, eliminate injuries and death ,etc. Furthermore, majority of the respondents agreed to the recommendation provided by the study to promote OSHP; management Penalties, provision of necessary safety gears, allocate a sum of money resources, management appreciation and motivation, etc. In conclusion, this paper will be beneficial to practitioners and academicians who study the practices of safety and health and work in construction site in order to improve the implementation of safety and health practices in the construction industry. Keywords: Promote, Construction project, OSHP, Safety and Health.